Mechanical characterization of parts produced by ceramic on‐demand extrusion process. Issue 3 (27th February 2017) - Ghazanfari, Amir; Li, Wenbin; Leu, Ming; Watts, Jeremy; Hilmas, Gregory
Abstract: Ceramic On‐Demand Extrusion (CODE) is an additive manufacturing process recently developed to produce dense three‐dimensional ceramic components. In this paper, the properties of parts produced using this freeform extrusion fabrication process are described. High solids loading (~60 vol%) alumina paste was prepared to fabricate parts and standard test methods were employed to examine their properties including the density, strength, Young's modulus, Weibull modulus, toughness, and hardness. Microstructural evaluation was also performed to measure the grain size and critical flaw size. The results indicate that the properties of parts surpass most other ceramic additive manufacturing processes and match conventional fabrication techniques.